Le sens de l’écart : la narration déconstruite dans les vidéos de Willie Doherty - Valérie Morisson (Cahiers de Narratologie)
In his video works, all tightly focused on the Northern-Irish conflict, Willie Doherty probes the perpetrator-victim dyad and denounces the truncated visual representation of the conflict by deconstructing the relation between image and sound. The texts uttered by the voice-over raise political issues relevant to post-conflict Ireland, whether it be victimhood, national trauma or the construction of collective memory. Multiple open-ended interwoven narratives accompany images without closing their interpretation.